Rancang Bangun Aplikasi Pembelajaran Desain Grafis Berbasis Multimedia Interaktif - Yulyanto; Rika Nugraha (Bulletin of Information Technology (BIT), 2022)
Abstract− This study aims to produce a graphic design learning media that is given to class XII students. The media is very effective in providing educational information to students, especially tutorial media. Because tutorial media is a visual interactive media tool to teach students to understand graphic design faster. In addition, at the high school / vocational school level, graphic design lessons have been given, but only use Corel Draw software, even though graphic design itself does not only use Corel Draw software. There are several examples of software used in graphic design, namely Photoshop, Adobe Illustrator. The results of this study obtained a new learning method that is ready to be used to teach graphic design material so that it can increase student motivation in the process of teaching and learning activities